An Analysis of the Impact of Agency Banking On Growth of Small and Medium-Scale Enterprises in Tharaka Nithi County - Kaburu, Lawrence Ngai (Kenyatta University, 2014)
During school opening days, we have witnessed long queues in the halls of our Commercial Banks arising from the last minute rush by the parents/guardians to pay school fees for their beloved children. In addition, the opening and closing hours of these commercial banks has continued to cause unknown havoc to small and medium scale enterprises who cannot access their services outside their normal but limiting operating hours. This has necessitated the proliferation of Agency Banking to complement the existing commercial banks. This study thus, mainly; assessed how low transaction cost by agency banks affect the growth of Small and Medium Scale Enterprises in Tharaka Nithi County; determined how customer relationship management by agency banks affect the growth of Small and Medium Scale Enterprises in Tharaka Nithi County; established how convenient financial services accessibility by agency banks affect the growth of Small and Medium Scale Enterprises in Tharaka Nithi County; and assessed how security of agency banks affect the growth of Small and Medium Scale Enterprises in Tharaka Nithi County. The study employed descriptive survey design with a sample size of 400 respondents. The primary data was collected using questionnaires. Data collected was edited, coded and analyzed using SPSS. In addition, the study conducted inferential statistics such as multiple regressions to measure the strength of the relationship between the dependent and independent variables. ANOVA was used to test the significance of the model and regression diagnostics were computed. The study deduced that customer relationship management affect the growth of SMEs business in Tharaka Nithi County to a great extent. The study also established that convenient financial services accessibility affect the growth of SMEs business in Tharaka Nithi County to a great extent. The study concluded that agency banking aid SMEs in saving money easily, agency banks are fast and have no queues like in banks, they also help SMEs avoid impulse buying, they are easily accessible and facilitate banking of money at night and weekends. The study recommended that banks should lower the transaction costs of agency banking. The bank should remove the deposit charges and instead come up with more elaborate way of recovering the commissions.
A Research Project Submitted to the School of Business in Kenyatta University in Partial Fulfillment of the Requirements for the Award of the Degree of Master of Business Administration in Finance